An analytical study on Brain Computer Interface Systems and its Applications - Patil, Apoorva (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network; Vol 4 No 1 (2020): Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
A brain-computer interface (BCI) is defined a communication system that allows us to translates brain activity into commands for computers and other devices. A BCI will allow users to act on their environment by using only brain activity, without using any kind of peripheral nerves and muscles. The main purpose of BCI research is to develop systems that help disabled individuals in communicating with other people. It also allows them to control artificial limbs, or to control their environment. Moreover, BCI aims at developing systems for usage in the field of assistive technology or multimedia communiqué. In this paper we give an introduction to some of the aspects of BCI research mentioned above, present a concrete example of a BCI system, and highlight recent application developments. How to cite this article: Patil A, Rane A. An Analytical study on Brain Computer Interface Systems and its Applications. J Adv Res Appl Arti Intel Neural Netw 2020; 4(1): 13-16.